Pengaruh Leverage, Profitabilitas, Struktur Modal, dan Ukuran Perusahaan pada Perusahaan Subsektor Perkebunan Kelapa Sawit yang Terdaftar di Bursa Efek Indonesia Periode 2020-2025 - Sinatrya, Tansa Bihisma; Hapsari, Ira Maya; Murdiati, Sri (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the determinants of firm value among palm oil plantation companies listed on the Indonesia Stock Exchange during the 2020–2025 period. Employing a quantitative approach, the study utilizes secondary data analyzed through multiple linear regression to examine the effects of leverage, profitability, capital structure, and firm size on firm value. The findings reveal that leverage, profitability, and firm size have a significant effect on firm value, whereas capital structure does not exert a significant influence. These results indicate that financial performance, debt policy, and firm size are key internal factors considered by investors in evaluating a company's prospects, thereby contributing to the formation of firm value in the capital market.